Seizure after chronic subdural hematoma evacuation: associated factors and effect on clinical outcome - Wu, Liang; Guo, Xufei; Ou, Yunwei; Yu, Xiaofan; Zhu, Bingcheng; Li, Yunfei; Liu, Weiming (Frontiers in Neurology, 2023)
Objective Chronic subdural hematoma (CSDH) is a common disease in neurosurgery, which usually occurs in the elderly. Seizure is one of the postoperative complications in CSDH patients and can affect patient outcomes. There is currently no consensus on whether antiepileptic drugs should be prescribed prophylactically. The aim of this study was to evaluate independent risk factors for postoperative seizures and unfavorable outcomes in CSDH patients. Methods We reviewed 1,244 CSDH patients who had undergone burr-hole craniotomy in this study. Patient clinical data, CT scan results, recurrence and outcome data were collected. We divided the patients into two groups based on whether they had a postoperative seizure. Percentages and χ2 tests were applied for categorical variables. Standard deviations and two-sided unpaired t-tests were applied for continuous variables. Stepwise logistic regression analyses were performed to identify the independent factors of postoperative seizures and unfavorable outcomes. Results The incidence of seizures after CSDH surgery was 4.2% in this study. There was no significant difference in recurrence rate between seizure and non-seizure patients (p = 0.948), and the outcome of seizure patients was significantly poor (p < 0.001). There are more postoperative complications in seizure patients (p < 0.001). Logistic regression analysis showed that the independent risk factors for postoperative seizures included drinking history (p = 0.031), cardiac disease (p = 0.037), brain infarction (p = 0.001) and trabecular hematoma (p < 0.001). The use of urokinase is a protective factor for postoperative seizures (p = 0.028). Hypertension is an independent risk factor for unfavorable outcome in seizure patients (p = 0.038). Conclusion Seizures after CSDH surgery were associated with postoperative complications, higher mortality and poorer clinical outcomes at follow-up. We believe that alcohol consumption, cardiac disease, brain infarction and trabecular hematoma are independent risk factors for seizures. The use of urokinase is a protective factor against seizures. Patients with postoperative seizures need more stringent management of their blood pressure. A prospective randomized study is necessary to determine which subgroups of CSDH patients would benefit from antiepileptic drugs prophylaxis.